Policing Africa: The US military and visions of crafting 'good order'. (April 2014) - Bachmann, Jan
Current Western security doctrines assert that state fragility, radicalization and humanitarian disasters in the global South feed into 'persistent conflict'. Such a scenario consequently requires a closely coordinated and integrated response from political and military actors. In this context, Western governments have introduced the concept of stabilization in their approaches to 'fragile' states. This article aims to understand the expanding activities of the US military in sub-Saharan Africa, which are conducted under the label of stability operations. It will be argued that the vast spectrum of activities under this label – from health projects to drone attacks – can be made comprehensible through the concept of policing, understood as processes of regulating communities with the aim of establishing 'good order'. Key pillars of the US military's stability operations operations doctrine – namely, a focus on the welfare of the population (on a par with the minimum use of force) as well as an extended preventative engagement – overlap with concerns of police power. Presented by security strategists as vulnerable to instability, sub-Saharan Africa has become an experimental ground for the US military, where ideas on stability operations are tested. Empirically, the article discusses two manifestations of stability operations that warrant an analysis through the concept of policing: US Africa Command's (AFRICOM) civil affairs projects and the US military's active involvement in ongoing conflicts.